Genome‐Wide Mapping and Analysis of Grapevine MicroRNAs and Their Potential Target Genes. Issue 2 (1st July 2015) - Jiu, Songtao; Zhu, Xudong; Wang, Jian; Zhang, Cheng; Mu, Qian; Wang, Chen; Fang, Jinggui
Abstract : MicroRNAs (miRNAs) are single‐stranded, nonprotein‐coding, endogenously expressed, small RNAs 19 to 25 nucleotides in length. Recognizing the lack of specific and systematic studies on genome‐wide mapping of grapevine ( Vitis vinifera L.) miRNAs, we conducted genome‐wide mapping of Vv‐miRNAs ( V. vinifera miRNAs), SB‐miRNAs ( V. vinifera L. 'Summer Black' miRNAs), and Va‐miRNAs ( V. amurensis Rupr. miRNAs). The mapping results revealed that many of miRNAs located within the intergenic region had independent transcription units. To further validate the mapping results and existence of miRNAs, 12 randomly selected precursors of miRNAs (pre‐miRNAs) were successfully cloned and sequenced. Subsequently, 15 conserved and 29 nonconserved intragenic (intronic, exonic) Vv‐miRNA genes, 24 nonconserved intragenic SB‐miRNA genes, and 23 nonconserved intragenic Va‐miRNA genes were labeled on the basis of their locations in host genes, and 15 MIRNA clusters were detected. Interestingly, five miRNA pairs, namely, Vv‐MIR395b and Vv‐MIR395c, Vv‐MIR482 and Vv‐MIRC13, Vv‐MIR172a and Va‐MIR057, SB‐MIR024 and Vv‐MIRC35, and Vv‐MIRC36 and Va‐MIR073 were clustered in the host genes GSVIVT01011558001, GSVIVT01008132001, GSVIVT01031524001, GSVIVT01028156001, and GSVIVT01024516001, respectively. To validate the existence of target genes and miRNA‐guided cleavage sites, 3′‐end product of four predicted target messenger RNAs were amplified by RNA ligase‐mediated 5′ rapid amplification of cDNA ends. In addition, we also conducted contrastive analysis on the genomic location of miRNAs and their potential target genes. Results showed that the order of priority of miRNA–target interaction may be less closely related with their genomic location. These findings could benefit some further study on grapevine functional genomics and will provide new insights into the regulatory mechanisms and evolution of miRNAs in Vitis species.